2007
DOI: 10.1117/12.717248
|View full text |Cite
|
Sign up to set email alerts
|

Novel concepts for ultrahigh-speed quantum-dot VCSELs and edge-emitters

Abstract: Advanced types of QD media allow an ultrahigh modal gain, avoid temperature depletion and gain saturation effects, when used in high-speed quantum dot (QD) vertical-cavity surface-emitting lasers (VCSELs). An anti-guiding VCSEL design reduces gain depletion and radiative leakage, caused by parasitic whispering gallery VCSEL modes. Temperature robustness up to 100°C for 0.96-1.25 m range devices is realized in the continuous wave (cw) regime. An open eye 20 Gb/s operation with bit error rates better than 10-12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 52 publications
(75 reference statements)
1
5
0
Order By: Relevance
“…It was found that the maximum temperature for lasing in our tunnel QDs-QW VCSELs is more than 140 o C. The highest lasing temperature of 150 o C was measured on another device (not shown on Figure 6). The light power reduces by about 50% only at 80 o C, the threshold current increases significantly at temperatures higher than 100 o C. The temperature robustness demonstrated in our VCSELs is comparable to and at some points exceeds characteristics presented by Ledentsov et al [8].…”
Section: Cw-operation Of Tunnel 3x (Qw-on-qds) Vcsels With Doped Dbrssupporting
confidence: 82%
See 3 more Smart Citations
“…It was found that the maximum temperature for lasing in our tunnel QDs-QW VCSELs is more than 140 o C. The highest lasing temperature of 150 o C was measured on another device (not shown on Figure 6). The light power reduces by about 50% only at 80 o C, the threshold current increases significantly at temperatures higher than 100 o C. The temperature robustness demonstrated in our VCSELs is comparable to and at some points exceeds characteristics presented by Ledentsov et al [8].…”
Section: Cw-operation Of Tunnel 3x (Qw-on-qds) Vcsels With Doped Dbrssupporting
confidence: 82%
“…We measured the temperature stability of our 3x (QWon-QDs) tunnel active media to compare with QDbased media [8] in VCSELs. Figure 6 shows the lightcurrent characteristics at various temperatures from -12 o C to + 140 o C of our 9x9 µm 2 tunnel QDs-QW VCSEL.…”
Section: Cw-operation Of Tunnel 3x (Qw-on-qds) Vcsels With Doped Dbrsmentioning
confidence: 99%
See 2 more Smart Citations
“…Integrated intracavity electrooptical and electroabsorption modulator based devices were attempted as an alternative to current modulated devices due to the increase of bandwidth and lowering of chirp that could be offered [8][9][10][11] but with limited success. It has really been the introduction of a duo-cavity architecture 7,12,13 that drastically improved bandwidth limits. Modulation of the device output in these cases was done by change of the field distribution inside the dual cavity device 12 , or by use of a variable resonance detuning to modulate top cavity transparency 7 .…”
Section: Introductionmentioning
confidence: 99%